Demands of World Cup competitions in elite women`s road cycling - Menaspà, P.; Sias, M.; Bates, G.; La Torre, A. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To describe the demand of recent World Cup (WC) races comparing top-10 (T10) and non-top-10 (N-T10) performances using power data. Methods: Race data were collected in 1-d World Cup races during the 2012-2015 road cycling seasons. Seven female cyclists completed 49 WC races, finishing 25 times in T10 and 24 times in N-T10. Peak power (1 s) and maximal mean power (MMP) for durations of 5, 10, 20, and 30 s and 1, 2, 5, 10, 20, 30, and 60 min expressed as power to weight ratio were analyzed in T10 and N-T10. The percentage of total race time spent at different power bands was compared between T10 and N-T10 using 0.75-W/kg power bands, ranging from <0.75 to >7.50 W/kg. The number of efforts in which the power output remained above 7.50 W/kg for at least 10 s was recorded. Results: MMPs were significantly higher in T10 than in N-T10, with a large effect size for durations between 10 s and 5 min. N-T10 spent more time in the 3.01- to 3.75-W/kg power band when compared to T10 (P=.011); conversely, T10 spent more time in the 6.75- to 7.50- and >7.50-W/kg power bands (P=.009 and .005, respectively) than N-T10. A significantly higher number of short and high-intensity efforts (=10 s, >7.5 W/kg) was ridden by T10 than N-T10 (P=.002), specifically, 46±20 and 30?±?15 efforts for T10 and N-T10, respectively. Conclusions: The ability to ride at high intensity was determinant for successful road-cycling performances in WC races.